2022
DOI: 10.1371/journal.ppat.1010451
|View full text |Cite
|
Sign up to set email alerts
|

Distinctive features of the respiratory syncytial virus priming loop compared to other non-segmented negative strand RNA viruses

Abstract: De novo initiation by viral RNA-dependent RNA polymerases often requires a polymerase priming residue, located within a priming loop, to stabilize the initiating NTPs. Polymerase structures from three different non-segmented negative strand RNA virus (nsNSV) families revealed putative priming loops in different conformations, and an aromatic priming residue has been identified in the rhabdovirus polymerase. In a previous study of the respiratory syncytial virus (RSV) polymerase, we found that Tyr1276, the L pr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 53 publications
0
13
0
Order By: Relevance
“…To distinguish between an effect on initiation versus early elongation, the compound was tested in an in vitro assay designed to examine effects on RNA synthesis from position 3C of the promoter 41 . Reactions were performed by preincubating full-length RSV L-P complexes with different concentrations of MRK-1 and then initiating reactions by adding an RNA oligonucleotide representing nucleotides 1–14 of the RSV trailer promoter, and ATP, UTP, and GTP, with radiolabeled GTP included as a tracer (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…To distinguish between an effect on initiation versus early elongation, the compound was tested in an in vitro assay designed to examine effects on RNA synthesis from position 3C of the promoter 41 . Reactions were performed by preincubating full-length RSV L-P complexes with different concentrations of MRK-1 and then initiating reactions by adding an RNA oligonucleotide representing nucleotides 1–14 of the RSV trailer promoter, and ATP, UTP, and GTP, with radiolabeled GTP included as a tracer (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Reactions to detect RNA synthesis products generated from position 3 of the tr promoter were performed with the following conditions: L-P complexes containing 300 ng RSV L or RSV L trunc were incubated in 25 µL reactions containing 50 mM Tris pH 7.5, 8 mM MgCl 2 , 5 mM DTT, 10% glycerol, 2 μM RNA oligonucleotide RSV tr 1-14 (Dharmacon), 500 μM each of ATP and UTP, and 10 µM GTP with 5 μCi [α- 32 P] GTP (3000 Ci/mmol) 41 . To analyze dinucleotide formation and elongation products in the presence of MRK-1, DMSO or various concentrations of inhibitor diluted in DMSO were included in the reaction mixtures.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Alternatively, transcription initiates at position +3 of the Le promoter. The +3 initiation at the TrC promoter only generates short (less than 25 nts) transcripts [ 18 , 19 , 20 , 21 , 22 ]. Fearns group demonstrated that the initiating nucleotides are loaded into RdRp independently of the template [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%